KARAKTERISASI EDIBLE FILM BERBAHAN DASAR EKSTRAK KARAGENAN DARI RUMPUT LAUT (Eucheuma cottonii) - Fardhyanti, Dewi Selvia; Julianur, Syara Sofia (Jurnal Bahan Alam Terbarukan, 2015)
Extraction process of carrageenan doing at 2 hours with temperature 80-90Â°C using sodium hidroxide with variant consentration of sodium hydroxide is 0,55N; 0,75N; 0,95N; 1,2N; 1,4N. The edible film makes with raw material carrageenan with 2 blended material is carrageenan composite with beeswax and the plasticizer sorbitol, along carrageenan with plasticizer sorbitol. The optimal yield from extraction process of carrageenan ressult at consentration of sodium hydroxide 1,2 N with value 43,42%. Optimal sulphate content get ressult at consentration of sodium hydroxide 0,45 N with value 10,28%. Optimal water content get ressult at consentration of sodium hydroxide 0,9 N with value 8,47%. Identification from FTIR to showing group of ester sulphate at spectrum 1227,67 cm-1. The identification chains of glicoxide at spectrum 1067,17 cm-1, the identification of group function 3,6 anhydrogalactose at spectrum 931,04 cm-1, and for group function galactose 4-sulphate can identification kind of kappa-carrageenan at spectrum 848,19 cm-1. Result of this ressearch showing the edible film makes with from blanded carrageenan composite and beeswax has best characteristic is high tensile strength with value 1,0755 MPa, percent elongation with 257,738% and miscible with value 15,45%.